A Palladium‐Nanoparticle and Silicon‐Nanowire‐Array Hybrid: A Platform for Catalytic Heterogeneous Reactions1. Issue 1 (15th November 2013) - Yamada, Yoichi M. A.; Yuyama, Yoshinari; Sato, Takuma; Fujikawa, Shigenori; Uozumi, Yasuhiro
Abstract We report the development of a silicon nanowire array‐stabilized palladium nanoparticle catalyst, SiNA‐Pd. Its use in the palladium‐catalyzed Mizoroki‐Heck reaction, the hydrogenation of an alkene, the hydrogenolysis of nitrobenzene, the hydrosilylation of an α, β‐unsaturated ketone, and the C‐H bond functionalization reactions of thiophenes and indoles achieved a quantitative production with high reusability. The catalytic activity reached several hundred‐mol ppb of palladium, reaching a TON of 2 000 000.